DESIGN OF AUTOMATIC BREAD CUTTING MACHINE - Rahmawaty, Made; Yolanda, Rieke; Hendriko, Hendriko (AUSTENIT, 2023)
Before being marketed, white bread will usually be cut first. Small to medium scale bread entrepreneurs still use conventional tools in the form of standard bread knives, whose use is still less effective. This bread cutting machine is designed for small to medium sized bakers to make their work easier and more efficient. This machine is designed using a vertical blade movement method with an AC motor as the driving force and is controlled using a sequential circuit. The initial process of this machine is to press the pushbutton, then place the bread on the bread tray which has a proximity sensor as a bread detector and the cutting process is carried out, when the sensor does not detect the presence of bread the machine will stop working automatically. Electronic system control is carried out sequentially which is more efficient in its application. From the test results obtained that the thickness of the bread is 12 mm. The main driver of the cutting is 1 phase and uses a dimer to adjust the rotational speed of the 1 phase motor. The cutting process with a maximum motor speed can cut 1 loaf for 38 seconds.